Literature study: Application of the Problem-Based Learning (PBL) learning model to improve problem-solving abilities and cognitive learning outcomes in biological sciences - Novi Febrianti; Sari Aisa (Universitas Ahmad Dahlan, 2023)
Students are required to be able to master 21st-century skills in learning biology. One of the demands of 21st-century skills is the ability to solve problems and biology learning outcomes. This study aims to analyze the effect of Problem-Based Learning model on problem solving ability and cognitive learning outcomes of biological science with literature study analysis. This research is a literature study with a narrative review type. The scientific articles used in this study amounted to 31 articles, consisting of 2 international journals, 18 accredited national journals, 3 unaccredited national journals, 3 proceedings, and 5 theses. The search for scientific articles was carried out through www.scholar.google.co.id and http://www.doaj.org. The data analysis technique was descriptive. The results showed that the Problem-Based Learning model had an effect on the ability to solve problems and cognitive learning outcomes of biological science.